Sources and Impact of Harmonic in Household and Office - Ismail, Daut, Prof. Dr.; Risnidar Chan, Bahaudin, Ir.; Norhaidar, Hashim; Surya Hardi, Ir.; Indra, Nisja (School of Electrical System Engineering, 2008)
Ekspo ini berlangsung di Dewan Sek. Men. Putra, Kangar, Perlis.